The Use of Euphemisms in the Book of â€œThe Alchemistâ€ by Paulo Coelho - Tarigan, Smirna Br; Marpaung, Marlin Steffi (Universitas Pendidikan Mandalika, 2023)
Euphemisms are a linguistic phenomenon whereby milder or courteous words are substituted for blunt or unpleasant expressions. This study focuses on the use of euphemisms and related expressions in Paulo Coelho's book,